PERAN EMPLOYEE ENGAGEMENT DAN DIGITAL CAPABILITY DALAM PRODUKTIVITAS PEGAWAI: PERSPEKTIF E-GOVERNMENT PT POS INDONESIA - Iwan Gunawan; Syamsul Hadi Senen (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2026)
Development of digital technology and the implementation of e-government demand adaptations in human resource governance. This study aims to analyze the roles of employee engagement and digital capability on the productivity PT Pos Indonesia employees within an e-government-based human capital strategy. Using a descriptive qualitative method, data were collected through in-depth interviews, observations, and documentation studies. The results indicate that employee engagement plays an optimal role in productivity, reflecting the importance of emotional involvement and employee commitment. Furthermore, digital capability proved crucial work effectiveness. The implementation of e-government serves as a strategic instrument to build digital capacity and employee engagement to create sustainable productivity. The implications research suggest that public organizations need simultaneously integrate digital competence policies with strategies to enhance employee engagement within the e-government system. This approach serves basis managerial decision-making and human resource policy formulation oriented toward increasing productivity, organizational resilience, and performance sustainability in digital era.